Cancellation of a Notary's Deed of Will that Fulfills the Elements of an Unlawful Act - Sukrisno, Wijayono Hadi; Arifulloh, Achmad (Jurnal Konstatering, 2025)
This study aims to examine the validity of a will deed made by a Notary when it meets the elements of an unlawful act and the Notary's responsibility in that context. The background of this study is the importance of the validity of a will deed as a legal document that determines the distribution of inheritance and the Notary's responsibility in ensuring that the deed is legally valid. The urgency of this study is directly related to the protection of heirs' rights and the integrity of the Notary profession. The research method used is normative juridical with a statutory approach and a case approach, using secondary data from literature studies and legal documents. The results of the study indicate that a will deed made in violation of legal provisions can be canceled by the court, as seen in the decision of the South Jakarta Religious Court No. 1920/Pdt.G/2018/PA.JS. Notaries have a great responsibility in ensuring that the will deed they make does not violate the law, and can be subject to civil, criminal, and administrative liability if proven guilty. The conclusion of this study emphasizes the importance of strict regulation and supervision of Notary practices, as well as effective law enforcement to protect the rights of heirs and maintain public trust in the Notary profession.